PERANCANGAN PROYEK RUMAH MAKAN DAN REST AREA TONGAS ASRI DENGAN PENDALAMAN HEALING ARCHITECTURE OLEH KONSULTAN ARSITEKTUR INTERIOR KUMO LIVING - Feline Victoria; Dyah Kusuma Wardhani (Universitas Ciputra Surabaya, 2023)
The tourism industry in Indonesia, especially domestic tourism, has experienced an increase after previously slumping during the COVID-19 pandemic. Mount Bromo, which is situated in the Probolinggo region, is one of the outdoor tourism destinations in Indonesia that has seen a rise in tourists. One of the access points to Mount Bromo is Raya Tongas Street, which is where the Tongas Asri Restaurant and Rest Area project is located and will be designed. The visitors who stop by Tongas Asri Restaurant are generally tired from the long road trip. By indulging guests’ five senses, the approach healing architecture used in this design project is anticipated to enhance the resting experience for guests. A location created with healing architecture aims to provide its occupants with a therapeutic and nurturing environment. It is intended that Kumo Living’s healing architecture will offer a way to positively stimulate each of the five human senses, namely sight, touch, smell, hearing, and taste, thereby producing a refreshing environment that helps visitors feel calm and happy again. Deepening healing architecture was selected for this project, with a stimulating environment as the final result of achieving a therapeutic environment in this project, such as nature connectedness, use of natural materials, use of restorative gardens, and designs that pamper visitors’ senses, thus, when stopping at the Restaurant and Rest Area, guests can rest and recuperate their physical and mental state.